Effect of Metformin as Add-on Therapy to Ibuprofen on the Disease Activity in Knee Osteoarthritis Patients: A Randomized, Double-Blind, Placebo-Controlled Trial (Faridpur Medical College Journal, 2026)
Background: Osteoarthritis (OA) is the most common type of arthritis. This condition is highly debilitating, encompassing various physical symptoms like pain, stiffness, loss of function, and disability that negatively impacts patient’s quality of life. Currently, there is no safe and effective therapy for OA. Metformin, a well-known drug used for type-II Diabetes Mellitus with excellent safety, shows anti-inflammatory properties. This study aimed to evaluate the effect of metformin as add-on therapy to ibuprofen in mild to moderate knee OA patients. Materials and Methods: Adults with knee pain, radiologically diagnosed with mild to moderate (grade II-III) knee OA, participated in this double-blind, randomized, placebo-controlled trial. Patients were assigned randomly to two groups. Both groups received Ibuprofen tablet 400 mg twice daily for two weeks as standard of care. As add-on therapy, one group (n = 35) received metformin extended release (ER) tablets 500 mg orally once daily, and the other group (n = 35) received an identical inert placebo tablets for 8 weeks. The outcome of treatment regimen was evaluated using the Knee Injury and Osteoarthritis Outcome Score (KOOS) questionnaire (normalized to scores of 0–100) at baseline, and at the end of 8th week.Results: Following a 8-weeks treatment, there was a significant improvement in scores of knee pain (P=0.01), activity of daily living (ADL) (P =0.028), and knee-related quality of life (QOL) (P=0.013) and total scores (P=0.02) of the KOOS questionnaire in the metformin group compared to the placebo group.Conclusion: Metformin as add-on therapy may have beneficial effects on improving knee pain, ADL, and QOL in mild to moderate knee OA patients. Faridpur Med. Coll. J. 2026;21(2):20-28